HOBBES AND SCIENTIFIC PRACTICE IN THE LEVIATHAN - Flórez Pabón, Campo Elías (International Journal of Research -GRANTHAALAYAH, 2018)
Hobbes in the seventeenth century (1639 - 1668), we must emphasize that suggests that taste or infatuation for science bodies (physical), because as he reminds us at the end of the leviathan in 1651; you are happy to return to their initial speculations about (De Corpore) natural bodies. (Hobbes Leviatã, 2003, p. 22). Such luck with these initial observations, we used to locate a context of discussion on the topic of science in the seventeenth century in England, specifically in one of the authors as Kuhn; in late modernity, they propose a new paradigm of scientific knowledge as had been developed by the Scholastics; perhaps its medieval metaphysical knowledge. However, much it has been written about this particular issue. Excuses are many references to the subject in the person of Hobbes; as one of the first authors who knew how to take the first steps on what we now know as science in particular. I do not use science or sacred metaphysical arguments; but he wanted to investigate or propose arguments away from religion to build what was known as truth, from other fundamental axes; different to the subject of God.